2013
DOI: 10.1063/1.4830045
|View full text |Cite
|
Sign up to set email alerts
|

In vivo virtual intraoperative surgical photoacoustic microscopy

Abstract: We developed a virtual intraoperative surgical photoacoustic microscopy system by combining with a commercial surgical microscope and photoacoustic microscope (PAM). By sharing the common optical path in the microscope and PAM system, we could acquire the PAM and microscope images simultaneously. Moreover, by employing a beam projector to back-project 2D PAM images onto the microscope view plane as augmented reality, the conventional microscopic and 2D cross-sectional PAM images are concurrently mapped on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Through the ex vivo and in vivo simulated surgical process monitored via i-PAOC-M, we successfully guided a needle under the skin layer and injected carbon particles at a desired location. Owing to PAM and OCT combined multimodal imaging, light-absorbing tissues and materials, e.g., a melanoma tumor, PVC, carbon particles, and surgical instrument as well as light-scattering tissues and materials, e.g., biological tissue, PVC, and surgical instruments, were visualized simultaneously, which is not possible with only one imaging modality, e.g., NIR-VISPAM and VISOCT [10,12,13]. For future study, several improvements will be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Through the ex vivo and in vivo simulated surgical process monitored via i-PAOC-M, we successfully guided a needle under the skin layer and injected carbon particles at a desired location. Owing to PAM and OCT combined multimodal imaging, light-absorbing tissues and materials, e.g., a melanoma tumor, PVC, carbon particles, and surgical instrument as well as light-scattering tissues and materials, e.g., biological tissue, PVC, and surgical instruments, were visualized simultaneously, which is not possible with only one imaging modality, e.g., NIR-VISPAM and VISOCT [10,12,13]. For future study, several improvements will be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Several comprehensive reviews on PAI can be found in the literature. 6,7,[17][18][19][20][21][22] Three types of PAI systems have been reported: (i) photoacoustic microscopy (PAM), [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] (ii) photoacoustic endoscopy (PAE), [40][41][42][43][44][45] (iii) photoacoustic tomography (PAT) or photoacoustic computed tomography (PACT). [46][47][48][49][50][51][52][53][54] In PAM, both the laser excitation and acoustic detection are focused (tightly or loosely depending on the configuration), and the dual foci are configured confocally to enhance measurement sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48][49][50][51][52][53][54] In PAM, both the laser excitation and acoustic detection are focused (tightly or loosely depending on the configuration), and the dual foci are configured confocally to enhance measurement sensitivity. Depending on whether the acoustic focus or optical focus is finer, PAM is categorized into acoustic-resolution PAM 32,[37][38][39] or optical-resolution PAM. 24,30,34 Subwavelength PAM was also demonstrated to achieve nanometric resolution in PAM systems.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, optical-resolution PAM (OR-PAM) is able to visualize label-free micro-scale images of oxy- and deoxyhemoglobin [ 7 ], melanin [ 8 ], DNA/RNA in cell nuclei [ 9 ], and so on. Due to its strong optical contrast and high optical resolution, OR-PAM has successfully been utilized in many biological studies and applications such as vascular biology [ 10 ], neurology [ 11 ], ophthalmology [ 12 ], intraoperative surgery [ 13 ] and so forth. The conventional OR-PAM systems utilize a special opto-ultrasound beam combiner for coaxial and confocal alignment of light illumination and ultrasound detection [ 14 ].…”
Section: Introductionmentioning
confidence: 99%